2022
DOI: 10.35762/aer.2021.44.1.6
|View full text |Cite
|
Sign up to set email alerts
|

RS-GIS Approach on Biomass Energy Potential Estimation of Sugarcane Residues in Medellin, Cebu

Abstract: The need to use alternative energy sources is driven by the continued rise in fossil fuel price, increasing population and energy demand most particularly in a developing country like the Philippines. Biomass resources such as sugarcane residues provide alternative means to utilize its untapped potential for renewable energy. The use of remote sensing technology and geographic information system enables detailed assessment on the quantification of its distribution, abundance and quality that will yield an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The research identified suitable locations to establish a decentralized biomass plant in the region. Similar studies have been reported by La Scalia et al (2022) , Galang et al (2022), and Ma et al (2022) in Southern Italy, northern Cebu province in the Philippines, and China, respectively.…”
Section: Introductionsupporting
confidence: 88%
“…The research identified suitable locations to establish a decentralized biomass plant in the region. Similar studies have been reported by La Scalia et al (2022) , Galang et al (2022), and Ma et al (2022) in Southern Italy, northern Cebu province in the Philippines, and China, respectively.…”
Section: Introductionsupporting
confidence: 88%